LA DIGNIDAD HUMANA COMO EJE FUNDAMENTAL DEL DERECHO A LA SALUD EN VILLAVICENCIO (2022)
This research addresses issues intrinsic to the Colombian health system, regarding the rights that are involved in providing this service, which has acquired an important place as a fundamental right, since the landmark ruling of the Constitutional Court in Ruling T-760 of 2008, with a fundamental tool given by the Constitution of 1991, the action of protection. The sources in the qualitative area are secondary sources brought in from academic texts and jurisprudence of the Constitutional Court that make up the theoretical part of the research. It is evident from the study carried out that the principle of human dignity is a fundamental pillar in the evolution towards the fundamental nature of the right to health. To conclude the above, it is appropriate to say that in practice the legal, jurisprudential and doctrinal scopes are short, before seeing a 29-year struggle, since the emergence of the 1991 Constitution, reflected on a material level.